Optimization of ultrasonic-assisted extraction parameters of Garcinia Cambogia and the biological activities of the extract - Nur Fashya Musa, 1984-, author 631606 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Thesis (Sarjana Falsafah (Kejuruteraan Bioproses))